DESIGN AND DEVELOPMENT OF LORAZEPAM RECTAL SUPPOSITORIES USING NATURAL POLYMERS. - Swapnil R. Nazarkar; Samrat A. Khedkar; Amol A. Ban; Rajendra G. Kharade; Rachana S. Das (Journal of Population Therapeutics and Clinical Pharmacology, 2019)
The Objective of present Research work was to develop different suppository bases in order to overcome drawbacks of traditional base and to study release of Phenytoin from developed bases. Cocoa butter was used as a base for one of the formulations while for other formulations combinations of suppository bases were prepared by fusion method. Hydrogenated vegetable oil was combined with cocoa butter, poloxamer 407 and polyethylene glycol 2000. Developed bases were evaluated for physicochemical parameters such as appearance, hardness, weight variation, hydroxyl value, etc and used for the preparation of lorazepam suppository. The suppositories of lorazepam were evaluated for physical parameters, drug content and in vitro drug release studies. The optimized suppository base was characterized by infrared spectroscopy and X-ray diffraction analysis. All the combination of suppository bases showed physical parameters within the prescribed range. Hydroxyl value of developed based showed in the range of 89.76-134.64.From the results, it is evident to prefer poloxamer 407 and polyethylene glycol 2000 with hydrogenated vegetable oil for faster release. The lorazepam suppositories also showed physical parameters within the prescribed limit. Formulation containing poloxamer 407 and hydrogenated vegetable oil showed 99.44% drug release at end of 120min with 61.83% dissolution efficiency and 45.38min mean dissolution time. The infrared spectroscopy indicated compatibility of drug with Excipients and X-ray diffraction and differential scanning calorimetry analysis showed reduction in degree of crystallinity of Phenytoin thus improving dissolution rate of drug. It can be concluded that poloxamer 407 and hydrogenated vegetable oil could be combined to deliver poorly soluble drug like Phenytoin